Peningkatan Minat Masyarakat Dalam Seni Dan Budaya Oleh Bengkel Kreatif Hello Indonesia (Studi kasus Bengkel Kreatif Hello Indonesia di Tangerang Selatan dengan Metode Kualitatif) - Nia Surya Amiati; Susie Perbawasari; Centurion Priyatna (Peneliti.net, 2023)
Creative workshops are a form of action taken by an organization to preserve Indonesian arts and culture which have begun to fade and prevent their extinction. This study aims to find out why Hello Indonesia Creative Workshop was formed, to analyze the increase in participants at Hello Indonesia Creative Workshop in increasing brand awareness through Social Media Hello Indonesia Creative Workshop, to analyze how Hello Indonesia Creative Workshop increases public interest in art and culture. The research method used is a qualitative approach. Research using in-depth interviews, observation and literature study. While the results of the research are to arouse the interest of young people by optimizing art and cultural education, holding regular traditional art performances, maximizing traditional arts in the midst of society, mixing and matching traditional art performances and inviting professional speakers. It can be suggested that the public, especially the younger generation, should be able to avoid and limit themselves against the negative impacts of globalization. because, if left unchecked, the negative impacts of globalization can gradually lead to the fading of the love for art that belongs to a region. Keywords: Public Interest in Art and Culture